Who is the Weakest Link? A Network Vulnerability Analysis Using a Congested Transport Assignment - Oded Cats; Sanmay Shelat (Findings)
We propose a user-equilibrium congested transit assignment model for a full-scan network vulnerability analysis by relying on the computations of network science indicators for infrastructure and service graphs. Model output include line-specific passenger loads. Furthermore, we propose a link criticality indicator for measuring the spatial extent of spill-over effects of link closures. In the case of the Amsterdam a disruption on the most critical link in the peak period induces 1,000 passenger-hours loss and a disruption spill overs on average to more than seven other links. Betweenness centrality and passenger loads do not offer good proxies for assessing link criticality.